Dermocosmetics’ industry in Brazil and Germany: a comparison of consumer preferences between these countries - Schwartzmann, Julia (2018)
This work examines the industry of Dermocosmetics or Cosmeceuticals, with a focus on the female consumer behavior. The scope of this work is the Brazilian and German markets, given that these two countries are among the biggest consumer markets of cosmetics and dermocosmetics (Euromonitor, 2014). Based on consumer behavior theories, previous studies about cosmetic markets, and an interview with a market specialist, we raised the most recurrent five topics, which were further investigated in order to understand the consumer behavior profiles of the Brazilian and the German women and, most importantly, understand the difference in preferences and trends between these two groups. The topics chosen where: (1) Preferences regarding the product origin (2) Preferences regarding the product type (3) What are the major concerns when choosing a product (I.E. esthetics, health etc) (4) On whom/what they rely to make the purchase decision (5) Concern with organic/sustainable products. This study consisted in the application of questionnaire to 72 Brazilian women and 68 German women to arrive to a valid sample of fifty Brazilian and fifty German women from 25 to 40 years old with similar acquisition power. Among the findings: German women tend to be more ethnocentric than Brazilians when choosing a cosmetics; there is a positive heurism towards French products in both populations; Brazilians make more use of advanced facial sunscreens and anti-agers, while Germans make more use of facial moisturizes and anti-agers and Brazilians use much more body products; German women are more driven by utilitarian motives, physiological needs and are more concern to their skin health, while Brazilians have more hedonic motives, are more concerned to the appearance; Brazilians are more looking to try new products while Germans are more traditional; both populations rely on dermatologists and friends/family to make the purchase, but Brazilians value and attend more dermatologists; Germans buy more organic/sustainable products than Brazilians, reasons were pointed as few options, lower quality, but both groups are willing to pay more if the quality is even.